Political economies of transnational fields: harmonization and differentiation in European diplomacy. Issue 2 (3rd April 2018) - Kuus, Merje
ABSTRACT: Political economies of transnational fields: harmonization and differentiation in European diplomacy. Territory, Politics, Governance . Focusing on Europe, this paper analyses diplomacy as an uneven transnational field. The field is uneven not only along the predictable lines of big and small states, but also along the lines of wealth and tradition that are customarily overlooked in diplomatic studies. The political economy of European diplomacy cannot be read off the map of states without considering cross-national patterns of economic and symbolic capital. The field is transnational in the sense that national, international and supranational elements blend in daily practice to create qualitatively new forms of diplomatic knowledge production. By analysing such uneven transnationalism, the paper brings greater empirical and conceptual specificity to our understanding of bureaucratic knowledge production. The empirical material focuses on diplomatic training. It is drawn from web-based sources and over 100 interviews with the professionals of diplomacy in Brussels and five national capitals. This 'peopled' lens enables a high-resolution analysis of diplomatic practice and thereby illuminates socio-spatial patterns that remain invisible in traditional state-based accounts. By unpacking in concrete terms what the oft-used phrase 'beyond the state' means in diplomatic training, the paper advances the study of bureaucratic knowledge production in geography and cognate fields.